Optimal location and sizing of capacitor placement in radial distribution system using Bacterial Foraging Optimization Algorithm. (October 2015) - Devabalaji, K.R.; Ravi, K.; Kothari, D.P.
Highlights: The new integrated approach of LSF and VSI is used to find the optimal location of capacitor. Proposed BFOA for solving capacitor placement. The load is varied form light load to peak load with step size of 1%. The generalized equation is derived to tune the capacitor size according to load changes. Abstract: This study introduces a new long term scheduling for optimal allocation of capacitor bank in radial distribution system with the objective of minimizing power loss of the system subjected to equality and in equality constraints. In the proposed method the new integrated approach of Loss Sensitivity Factor (LSF) and Voltage Stability Index (VSI) are implemented to determine the optimal location for installation of capacitor banks. Bacterial Foraging optimization algorithm (BFOA) is proposed to find the optimal size of the capacitor banks. The proposed method is applied on IEEE 34-bus and 85-bus radial distribution system with all possible load changes. The load is varied from light load (50%) to peak load (160%) with a step size of 1% and optimization procedure is followed to entire period. The generalized equation obtained from the curve fitting technique is very much helpful for the Distribution Network Operators (DNOs) to adjust the capacitor size according to the load changes. The simulated results demonstrate well the performance and effectiveness of the proposed method.